PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS VIIIG SMPN 1 PIYUNGAN - AMANAH AMANAH (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2023)
The aim of the research is to improve student learning outcomes in Maritime Economics and Agriculture through the application of the Problem Based Learning learning model. This research was conducted at Piyungan 1 Public Middle School in the Even semester of the 2021/2022 Academic Year. The subjects of this study were students of class VIIIG, totaling 30 students consisting of 14 girls and 16 boys. This research is a classroom action research (PTK) which consists of 2 cycles, Cycle I, and Cycle II, each cycle consisting of two meetings. The stages of this research include the stages of planning, implementing, observing, and reflecting. Data collection techniques include observation and learning achievement tests. Data analysis used quantitative descriptive data analysis. The results showed an increase in knowledge test results, the average value in the first cycle of 76.67 increased to 84.00 in the second cycle. The number of students who achieved completeness was 22 (73.33%) students in cycle I increased to 27 (90%) students in cycle II, there were still 3 students in cycle II who had not completed. The results of the learning test achievement of class VIIIG students in maritime economics and agriculture material, the minimum class average score is ?77, the classical completeness has exceeded 85%. The results of the knowledge assessment reach the Minimum Completeness Criteria of 90%. The conclusion in this study is that the application of the Problem Based Learning learning model can improve social studies learning outcomes. ABSTRAKTujuan dari penelitian adalah meningkatkan hasil belajar siswa pada materi Ekonomi Maritim dan Agrikultur melalui penerapan model pembelajaran Problem Based Learning. Penelitian ini dilaksanakan di SMP Negeri 1 Piyungan pada semester Genap Tahun Pelajaran 2021/2022. Adapun subjek dari penelitian ini adalah siswa kelas VIIIG yang berjumlah 30 siswa terdiri 14 perempuan dan 16 laki-laki. Penelitian ini merupakan penelitian tindakan kelas (PTK) yang terdiri dari 2 Siklus, Siklus I, dan Siklus II setiap siklus terdiri dari dua pertemuan. Adapun tahapan penelitian ini meliputi tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik pengumpulan data meliputi observasi dan tes hasil belajar. Analisis data menggunakan analisis data deskriptif kuantitatif. Hasil penelitian menunjukkan peningkatan hasil tes pengetahuan, nilai rata- rata pada siklus I sebesar 76,67 meningkat menjadi 84,00 pada siklus II. Jumlah siswa yang mencapai ketuntasan 22(73,33%) siswa pada siklus I naik menjadi 27(90%) siswa pada siklus II, masih ada 3 siswa pada siklus II yang belum tuntas. Hasil pencapaian tes belajar siswa kelas VIIIG pada materi ekonomi maritim dan agrikultur nilai rata-rata kelas minimal ?77, ketuntasan klasikal telah melampaui 85%. Hasil penilaian pengetahuan mencapai Kriteria Ketuntasan Minimal sebesar 90%.Kesimpulan dalam penelitian ini penerapan model pembelajaran Problem Based Learning dapat meningkatkan hasil belajar IPS.